PENGARUH NILAI BUDAYA TERHADAP PROSES KONSELING - Iche Lisa Sismona (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
highlighting the significance of cultural beliefs, norms, and values in shaping individuals' perspectives and interactions in society. The cultural values held by a group impact how individuals view the world, interpret issues, seek solutions, and engage with others, emphasizing the significant influence of cultural values on the counseling process. Multicultural counseling is defined as a dynamic intercultural relationship where participants with different cultural backgrounds engage, underscoring the importance of understanding and respecting cultural diversity. Counselors must navigate diverse clients with varying thoughts, feelings, customs, personalities, language, and beliefs, requiring them to facilitate, reflect, consult, and monitor progress to enhance their effectiveness in counseling services. By integrating cultural values into counseling interventions, counselors can help strengthen clients' cultural identity, fostering trust and mutual understanding essential for successful counseling outcomes. Implementing culturally sensitive communication skills essential in multicultural counseling provides holistic support for clients from various cultural backgrounds, promoting inclusivity, empathy, and effective intercultural communication skills. Ultimately, embracing cultural diversity and acknowledging the impact of cultural values in the counseling process enables counselors to build stronger therapeutic relationships and facilitate clients' growth and recovery effectively